Deadly COVID-19 among the elderly: Innate immune memory helping those most in need - Sohrabi, Yahya (Med (N Y), 2021)
Age is a key risk factor associated with the severity of symptoms caused by SARS-CoV-2, and there is an urgent need to reduce COVID-19 morbidity and mortality in elderly individuals. We discuss evidence suggesting that trained immunity elicited by BCG vaccination may improve immune responses and can serve as a strategy to combat COVID-19 in this population.